Request of the Spanish Government for the technical assistance of the League in the study of measures for providing food supplies for refugees (report) - Bray, Denys, 1875-1951
1938-11-03 032-0199-003 - 2 - should a suitable opportunity occur.x He observed that the problem called for careful consideration, and suggested that the most practical step to take might be to send some competent persons to Spain to take stock of the extent of the problem and the possibilities of a solution. The Council thereupon adopted the following resolution:- "The Council, "In response to the request made by the Spanish Government for the technical assistance of the League in providing food supplies for refugees in Spain: "Authorises the Secretary-General to institute a preliminary enquiry on the spot and to charge the expenses thereof, to an amount not exceeding 45,000 Swiss francs, to item 2(c)(i) of the budget for 1938: 'Council: Unforeseen Expenditure (subject to special vote of the Council); political expenditure'." The Secretary-General drew attention at the same time to the last paragraph but one of the Spanish Government's letter of which he asked the Council to take note. In virtue of the above resolution of the Council, the Secretary-General invited Sir Denys Bray, K.C.S.I., K.C.I.E., sometime Foreign Secretary to the Government of India, subsequently Member of the Council of India, assisted by Mr. Lawrence Webster, sometime Director of Save the Children Fund in Bulgaria and later Assistant to the League of Nations' Commissioner for the settlement of refugees in that country, to undertake the preliminary enquiry contemplated and to proceed to Spain immediately for that purpose. Sir Denys Bray and Mr. Webster, for whose prompt acceptance of his invitation the Secretary-General expresses his gratitude, conducted a personal investigation of conditions in Spain during the period October 9th - 27th and have now submitted their report, which the Secretary-General has the honour to communicate to the Council herewith. This resolution read as follows: "The Council: "Notes that there are problems of a humanitarian character in connection with the present situation, in regard to which co-ordinated action of an international and humanitarian character is desirable as soon as possible; "Recognises, further, that, for the reconstruction which Spain may have to undertake, international assistance may also be desirable; "And authorises the Secretary-General to make available the assistance of the technical services of the League of Nations should a suitable opportunity occur." 292/946/32/199(ii)